Lipid analysis of the plasma membrane and mitochondria of brewer's yeast - Blagović, B; Rupcić, J; Mesarić, M; Marić, V (Folia microbiologica, 2005)
The plasma membrane and mitochondria of bottom fermenting brewer's yeast obtained as a by-product of industrial beer production were isolated and the lipid fraction was analyzed. The phospholipid content accounted for 78 mg/g protein in the plasma membrane and 59 mg/g protein in the mitochondria. Major phospholipids in both preparations were phosphatidylinositol, phosphatidylcholine and phosphatidylethanolamine but their proportions differed significantly. In the plasma membrane phosphatidylinositol, and in the mitochondria phosphatidylcholine were present in the highest concentration (37 and 30%, respectively). The main classes of neutral lipids (triacylglycerols, ergosterol, squalene and steryl esters) were twice more abundant in the plasma membrane than in the mitochondria (61 and 33 mg/g protein, respectively). A characteristic of the neutral lipid composition of both organelles was the low content of ergosterol (12 and 7 mg/g protein, respectively) and a high content of squalene (25 and 22 mg/g protein). The main feature of the fatty acid composition of both organelles was the preponderance of saturated fatty acids (78 and 79%, respectively), among which palmitic acid was the principal one. The most expressed characteristics of lipid fractions of the analyzed plasma membranes and mitochondria, high concentration of squalene and preponderance of saturated fatty acids are the consequences of anaerobic growth conditions. The lack of oxygen had possibly the strongest effect on the lipid composition of the plasma membranes and mitochondria of bottom fermenting brewer's yeast.
Keywords: fosfolipidy; skvalen; Saccharomyces cerevisiae; chromatografie plynová; Squalene; membránové lipidy; Phospholipids; buněčná membrána; Membrane Lipids; mitochondrie; Chromatography, Gas; Mitochondria; Fatty Acids; mastné kyseliny; Cell Membrane